The Relationship Learning Education of Religion Islamic on Honest Behavior In Class 8 Junior High School of Ibnu Aqil Bogor - Dahlan R, M.; Arif, Suyud; Ma’arif, Muhamad Syamsul (Universitas Malikussaleh, 2019)
Islamic religious education is an effort made to develop all human potential both physically and mentally so that the formation of a whole Muslim person. Islamic education places humans as creatures created by Allah SWT. Thus, Islamic religious education is important in shaping the character of students, one of which is an honest character. The aim to be achieved is to find out the relationship between learning Islamic religious education towards students' honest behavior. The research method used is quantitative research by random sampling as a research sample selection technique. School chosen as research is a school that has implemented the 2013 Class 8 curricula in Ibnu Aqil Middle School, Bogor Regency. based on this, 54 students were selected as the study sample consisting of classes A to F, which each class took 9 people as the study sample. Data collection was done using a questionnaire based on a Likert scale assessment. Before being used to collect the data needed in research, the validity of the instrument was tested using SPSS. The results of the study explains that there is a significance of 0,000 less than 0.05 which means (Ho) is rejected, and there is a correlation value of 0.679 which means (Ha) is accepted, which means there is a significant positive relationship between learning Islamic education (variable X) on behavior honest students (variable Y), it can be concluded that learning Islamic education has a significant relationship to honest behavior in Ibn Aqil Middle School, Bogor Regency.